2020
DOI: 10.17485/ijst/v13i29.976
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of reconfigurable DCT based adaptive PST techniques in OFDM communication system using interleaver encoder

Abstract: Objectives: To propose Reconfigurable Discrete Cosine Transform (RDCT) in Orthogonal Frequency Division Multiplexing (OFDM) high speed communication system to improve efficient spectrum utilization and mitigation of jitter, selective fading effects. The adaptive PTS method reduces Inter-Carrier-Interference (ICI), Inter-Symbol-Interference (ISI), PAPR and the computational intricacy of the communication system. To analyse and compare the performance of proposed Reconfigurable method with existing conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Related Works Optimization Method/Flow (7) , (10) MBFFs Logic optimization (9) MBFFs Pre-placement optimization (8) Register bank placement optimization (11) , (12) , (13) MBFFs post-placement optimization…”
Section: Table 1 List Of Mbffs Flow Design Optimization Methods and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Related Works Optimization Method/Flow (7) , (10) MBFFs Logic optimization (9) MBFFs Pre-placement optimization (8) Register bank placement optimization (11) , (12) , (13) MBFFs post-placement optimization…”
Section: Table 1 List Of Mbffs Flow Design Optimization Methods and Related Workmentioning
confidence: 99%
“…In SOC design the dynamic power consumption is dominated and 75% of power is contributed to the total power of the design (2) . Recent researches have introduced many approaches to reduce to switching rate in the clock network such as register placement optimization, buffer sizing [ (3)(4)(5) , register banks (6) , multi-bit flipflops (MBFFs), or applying multi-bit registers (7)(8)(9)(10)(11)(12)(13)(14)(15) . The concept of making a flip-flop of 2 bit from merging -bit flip-flops of two 1 bit is shown in Figure . 1.…”
Section: Introductionmentioning
confidence: 99%
“…The drawback of this approach is that it creates overload to Cluster heads where huge number of sensors are deployed near to it. The authors in the study (27,28) , have used PSO technique for clustering and communication in the wireless sensor network and it is also been highlighted that the PSO efficiently optimizes the network lifetime of WSN, however the study in (29) shows that PSO technique suffers from a problem called curse of dimensionality. The study in (30) has showed that the Differential Evolution (DE) techniques proves to be the best for clustering among all other conventional methods in WSN (31) , it also states that DE technique is simple, consisting of fewer parameters, reliable and provides the optimum solutions in each run.…”
Section: Related Workmentioning
confidence: 99%
“…Where ๐‘‰ ๐‘” is presented generated voltage and ๐ผ ๐‘” is described as a generated current. Consider there is no attenuation in system, then the equation ( 6) can be represented as given in (7).…”
Section: Algorithm Of Maximum Power Trackingmentioning
confidence: 99%
“…Nevertheless, when speed of the wind drops lower than the minimum needed a minor gas turbine model is presented as a hold up or a backup source to sustain electricity of a nonstop stream mode [3]- [5]. The power of wind which is maximum is extracted from the wind power system controller and it supplies to the given grid with a worthy quality [6], [7]. A flow controller of power is utilized to maintain the supplied electricity ๏ฒ ISSN: 2088-8694 from both sources of power.…”
Section: Introductionmentioning
confidence: 99%